2014
DOI: 10.3389/fpsyg.2014.00818
|View full text |Cite
|
Sign up to set email alerts
|

A fan effect in anaphor processing: effects of multiple distractors

Abstract: Research suggests that the presence of a non-referent from the same category as the referent interferes with anaphor resolution. In five experiments, the hypothesis that multiple non-referents would produce a cumulative interference effect (i.e., a fan effect) was examined. This hypothesis was supported in Experiments 1A and 1B, with subjects being less accurate and slower to recognize referents (1A) and non-referents (1B) as the number of potential referents increased from two to five. Surprisingly, the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Specifically, the presence of multiple gender matched licensors in the grammatical conditions (e.g., The harpist that the diva … after playing… herself ) increased reading times at the gerundive verb, and later facilitated reading times in the same conditions at the reflexive. These effects were unexpected, and we believe that the effect of distractor at the gerundive might reflect a “fan” effect ( Anderson, 1974 ; Anderson and Reder, 1999 ), which can arise in grammatical contexts when multiple items match the retrieval cues ( Badecker and Straub, 2002 ; Autry and Levine, 2014 ; but cf. Chow et al, 2014 ).…”
Section: Methodsmentioning
confidence: 90%
“…Specifically, the presence of multiple gender matched licensors in the grammatical conditions (e.g., The harpist that the diva … after playing… herself ) increased reading times at the gerundive verb, and later facilitated reading times in the same conditions at the reflexive. These effects were unexpected, and we believe that the effect of distractor at the gerundive might reflect a “fan” effect ( Anderson, 1974 ; Anderson and Reder, 1999 ), which can arise in grammatical contexts when multiple items match the retrieval cues ( Badecker and Straub, 2002 ; Autry and Levine, 2014 ; but cf. Chow et al, 2014 ).…”
Section: Methodsmentioning
confidence: 90%
“…The retrieval interference account also standardly predicts a slowdown for gender-marked reflexives, although several studies reported a speedup (Sturt, 2003 , Experiment 1; Cunnings and Felser, 2013 , Experiment 2; Cunnings and Sturt, 2014 ; Baumann and Yoshida, 2015 ; Jäger et al, 2015a , Experiment 3). Similarly, in a study on anaphoric noun phrases, Autry and Levine ( 2014 ) found that increase in number of potential referents (from two to five) decreased rather then increased reading times at the noun phrase.…”
Section: Experiments 2a: Russian Reflexives Reflexive Precedes Thementioning
confidence: 87%
“…Similarity-based interference, i.e., the failure to successfully distinguish a target from similar competitors in retrieval, has now been well documented both in general memory manipulations (Nairne, 2002 ; Öztekin and McElree, 2007 ) and in language processing contexts (Lewis, 1996 ; Gordon et al, 2001 , 2002 , 2004 , 2006 ; Van Dyke and Lewis, 2003 ; Van Dyke and McElree, 2006 , 2011 ; Van Dyke, 2011 ; Autry and Levine, 2014 , among others). Dual task paradigms combine the two, so that a subject attempts to retain a list of words in working memory while processing a separate sentence for comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…As a final terminological note, the present use of “interference” diverges somewhat from a common use in the literature, in which the distractor is not a grammatical antecedent, or otherwise inaccessible (e.g., Van Dyke, 2007 ; Phillips et al, 2011 ). If both nouns in the matrix are acceptable as antecedents, the manipulation might be best cast in terms of a “fan effect” in which multiple non-referents interfere with dependency resolution (Anderson, 1974 ; Anderson and Reder, 1999 ; Autry and Levine, 2014 ). However, as the effects in either case would ideally be driven by the same underlying types of retrieval mechanisms, I retain the use of interference here, in hopes of expanding the empirical range of strongly biased, though not strictly speaking ungrammatical, structural preferences.…”
Section: Introductionmentioning
confidence: 99%